Trauma and romance in contemporary British literature - Ganteau, Jean-Michel.; Onega Jaén, Susana (New York : Routledge, 2013)
"Drawing on a variety of theoretical approaches including trauma theory, psychoanalysis, genre theory, narrative theory, theories of temporality, cultural theory, and ethics, this book breaks new ground in bringing together trauma and romance, two categories whose collaboration has never been addressed in such a systematic and in-depth way. The volume shows how romance strategies have become an essential component of trauma fiction in general and traumatic realism in particular. It brings to the fore the deconstructive powers of the darker type of romance and its adequacy to perform traumatic acting out and fragmentation. It also zooms in on the variations on the ghost story as medium for the evocation of trans-generational trauma, as well as on the therapeutic drive of romance that favors a narrative presentation of the working-through phase of trauma. Chapters explore various acceptations and extensions of psychic trauma, from the individual to the cultural, analyzing narrative texts that belong in various genres from the ghost story to the misery memoir to the graphic novel. The selection of primary sources allows for a review of leading contemporary British authors such as Peter Ackroyd, Martin Amis, Ian McEwan, Salman Rushdie, Graham Swift, Sarah Waters and Jeanette Winterson, and of those less canonical such as Jackie Kay, Alan Moore and Dave Gibbons, Justine Picardie, Peter Roche and Adam Thorpe. "--
pt. I. Ghost stories, repetition and the transmission of trauma -- pt. II. Narratives of distress and individual trauma -- pt. III. Collective trauma, history and ethics -- pt. IV. Therapeutic romance.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: English fiction -- 21st century -- History and criticism; Wounds and injuries in literature; Psychic trauma in literature; Electronic books